BETWEEN MILITARY AND ENVIRONMENTAL DEMOCRACY: Looking at The Citarum Military Task Force through The Concept of Environmental Democracy - Mustofa, Mustabsyirotul Ummah; Pane, Dini Gabriella Debora; Tedy, Alifia; Amelia, Diva Aura (Department of Government, FISIP, Universitas Padjadjaran, 2023)
The status of pollution and damage in the Citarum River Basin (DAS) is considered to be critical. In the effort to accelerate and continue the control of the Citarum River Watershed, there are indications that the government does not involve the community and only relies on the role of the military. This study aims to see where the military and civilian actors fit into the concept of environmental democracy. This study uses a qualitative approach to achieve a comprehensive theoretical analysis of environmental democracy. The results of this study show that the existence of the military role in the Citarum Harum Task Force has yet to be well implemented by the ranks of the Citarum Harum task force. The military’s dominance appears too strong throughout Citarum Harum's activities. There are indications of power imbalance in civil-military relations, which posed threats to civil rights. The involvement of the military dominates almost all aspects of the Citarum watershed policymaking. Therefore, for the sake of democracy, the military role should be reduced to make optimal public participation.